Mating barriers between genetically divergent strains of the parasitic nematode Haemonchus contortus suggest incipient speciation. Issue 7 (June 2019) - Sargison, Neil D.; Redman, Elizabeth; Morrison, Alison A.; Bartley, David J.; Jackson, Frank; Hoberg, Eric; Gilleard, John S.
Graphical abstract: Highlights: We investigated the ability of genetically divergent Haemonchus contortus strains to interbreed. Overlapping inter-strain morphological and morphometric variation was observed. Co-infecting strains interbreed, but proportions of F1 progeny depart from Mendelian expectations. Post-zygotic incompatibility in hybrid progeny of paternal parents is consistent with incipient speciation of MHco10(CAVR). Our results have implications for ecology of anthelmintic resistant parasite populations. Abstract: Haemonchus contortus, in common with many nematode species, has extremely high levels of genetic variation within and between field populations derived from distant geographical locations. MHco10(CAVR), MHco3(ISE) and MHco4(WRS) are genetically divergent H. contortus strains, originally derived from Australia, Kenya and South Africa, respectively, that have been maintained by numerous rounds of in vivo experimental infection of sheep. In order to explore potential pre-zygotic competition or post-zygotic incompatibility between the strains, we have investigated the ability of MHco10(CAVR) to interbreed with either MHco3(ISE) or MHco4(WRS) during dual strain co-infections. Sheep were experimentally co-infected with 4000 infective larvae (L3 ) per os of the MHco10(CAVR) strain and an equal number of either the MHco3(ISE) or the MHco4(WRS) strain L3 . The adult worm establishement rates and the proportions of F1 progeny resulting from intra- and inter-strain mating events were determined by admixture analysis of microsatellite multi-locus genotypes. Although there was no difference in adult worm establishment rates, the proportions of F1 progeny of both the MHco10(CAVR) × MHco3(ISE) and MHco10(CAVR) × MHco4(WRS) dual strain co-infections departed from Mendelian expectations. The proportions of inter-strain hybrid F1 progeny were lower than the expected 50%, suggesting either pre-zygotic competition or post-zygotic incompatibility between the co-infecting strains. To investigate this further, both eggs and hatched L1 of broods from single adult female worms recovered from each dual co-infection were genotyped. Unhatched eggs from the broods revealed no inter-strain hybrid genotype deficit, suggesting there is no pre-zygotic competition between the strains. In contrast, there was a deficit in L1 inter-strain hybrid genotypes in the broods derived from MHco3(ISE) or MHco4(WRS) maternal parents, but not from MHco10(CAVR) maternal parents. This suggests that hybrid progeny of MHco10(CAVR) paternal parents have reduced post-zygotic development and/or viability consistent with incipient speciation of the MHco10(CAVR) strain. The presence of mating barriers between allopatric H. contortus strains has important implications for parasite ecology, including the ability of newly introduced anthelmintic-resistant parasite populations to compete and interbreed with populations already established in a region.